Sustainability requirements for connected health applications. Issue 7 (28th November 2017) - Ouhbi, Sofia; Fernández‐Alemán, José Luis; Toval, Ambrosio; Rivera Pozo, José; Idri, Ali
Abstract: Connected health applications are efficient tools to improve health care services. The aim of this paper is to define a reusable requirements repository (catalog) for sustainable connected health applications based on the main related software engineering standards, e‐health technology standards, and literature. The catalog contains requirements which cover the individual, social, environmental, and technical dimensions of sustainability. The requirements presented in this paper can be very useful to connected health application stakeholders and can be adapted to specific m‐health applications. Moreover, the requirements catalog can be used to generate a checklist of requirements to evaluate and audit connected health applications. An application example is presented to show that the evaluation of connected health applications using the generated checklist is realistic.